2018
DOI: 10.1111/jfbc.12734
|View full text |Cite
|
Sign up to set email alerts
|

Protein hydrolysate from salmon frames: Production, characteristics and antioxidative activity

Abstract: Protein hydrolysates from two forms of salmon frames named “chunk” and “mince” were produced and characterized. Both samples were subjected to hydrolysis using alcalase and papain at 1%–3% (w/w protein) for 0–240 min. Hydrolysate prepared with either protease at 3% for 180 min had the solid yield of 24.05%–26.39%. Hydrolysates contained 79.20%–82.01% proteins, 6.03%–6.34% fat, 9.81%–11.09% ash, and 4.02%–5.80% moisture. Amino acid profile showed that all hydrolysates had glutamic acid/glutamine (113.45–117.56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 52 publications
(86 reference statements)
7
71
0
1
Order By: Relevance
“…The more the hydrolysis, the higher the extent of degradation of native protein structure and the more the exposure of hidden hydrophobic peptides causing bitterness are attained (Fu, Liu, Hansen, Bredie, & Lametsch, 2018). This claim was reconfirmed by Idowu et al (2018), who reported the influence of DH on bitterness of FPH from salmon frame. FPH from salmon frame produced with Alcalase with higher DH possessed higher hydrophobic amino acid and bitterness than its counterpart prepared using papain with less DH.…”
Section: B It Terne Ss Of Fphmentioning
confidence: 84%
See 4 more Smart Citations
“…The more the hydrolysis, the higher the extent of degradation of native protein structure and the more the exposure of hidden hydrophobic peptides causing bitterness are attained (Fu, Liu, Hansen, Bredie, & Lametsch, 2018). This claim was reconfirmed by Idowu et al (2018), who reported the influence of DH on bitterness of FPH from salmon frame. FPH from salmon frame produced with Alcalase with higher DH possessed higher hydrophobic amino acid and bitterness than its counterpart prepared using papain with less DH.…”
Section: B It Terne Ss Of Fphmentioning
confidence: 84%
“…However, peptides containing bulky hydrophobic groups toward their C-terminal, have been regarded as the major causes of bitterness (Yarnpakdee et al, 2015). Hydrophobic groups of amino acids responsible for bitterness are Trp, Phe, Iso, Try, Val, and Leu (Idowu et al, 2018). It was documented that bitterness was attributed to hydrophobic amino acids in peptides, irrespective of amino acid sequence (Matoba & F I G U R E 1 Biological activities of bioactive peptides Hata, 1972).…”
Section: B It Terne Ss Of Fphmentioning
confidence: 99%
See 3 more Smart Citations